Risk factors associated with substance use in female victims of abuse living in a context of poverty - Rivas Rivero, Esther; Bonilla-Algovia, Enrique; Vázquez, Jose Juan (Anales de Psicología / Annals of Psychology, 2020)
The work analyzes the relationship between the suffering of stressful life events and the excessive consumption of alcohol and drugs in 136 women victims of gender violence in Nicaragua. The data was obtained from a heteroapplied structured interview designed for this purpose, which collects stressful life events suffered by the victims throughout their lives. The results show that those who suffered different episodes of violence since childhood consumed alcohol and drugs in excess. In addition, the greatest predictor for alcohol and drug use is among those who suffered sexual abuse before age 18. On the other hand, the Odds Ratio analyzes indicate an increased risk for the consumption of substances when the abuse occurred at an early age. Despite the relevance for the health of the victims, there are few devices in Nicaragua with which to assist victims of gender violence towards recovery processes, especially for those who have developed coping strategies related to excessive substance use.